1993
DOI: 10.1109/10.250580
|View full text |Cite
|
Sign up to set email alerts
|

A new method for measuring small local vibrations in the heart using ultrasound

Abstract: In order to diagnose ventricular dysfunction based on the acoustic characteristics of the heart muscle of the ventricle, it is necessary to detect vibration signals from various parts of the ventricular wall. This is, however, difficult using previously proposed ultrasonic diagnostic methods or systems. The reason is that the amplitude of the cardiac motion is large during one beat period which produces large fluctuations in the transit time required for ultrasonic waves to travel from the transducer to the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…A significant compliance increase has been reported with age (Rogers et al 2001) and with atherosclerosis (Wang et al 2000). Moreover, further evidence of rapid transient motion in cardiovascular tissues was found by Kanai et al (1993; inside the heart. They found that a transient mechanical wave was generated at the root of the aortic valve, due to a strong mechanical effect upon valve closure.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…A significant compliance increase has been reported with age (Rogers et al 2001) and with atherosclerosis (Wang et al 2000). Moreover, further evidence of rapid transient motion in cardiovascular tissues was found by Kanai et al (1993; inside the heart. They found that a transient mechanical wave was generated at the root of the aortic valve, due to a strong mechanical effect upon valve closure.…”
Section: Introductionmentioning
confidence: 92%
“…Kanai et al (1993) developed a customized ultrasound system that used a small number of ultrasound beams distributed over a large field-of-view. Using this technique, they were able to simultaneously measure the tissue motion in the myocardium using 16 ultrasound beams at a high frame rate (450 Hz).…”
Section: Introductionmentioning
confidence: 99%
“…Transient waves were also detected and imaged during propagation, clockwise or counterclockwise depending on the cardiac phase, along the myocardial wall. Those waves could not be detected by standard 2-d echocardiography, which typically operates at 60 to 90 Hz or 3-d echocardiography (15)(16)(17)(18)(19)(20). Fig.…”
Section: Electromechanical Wave Imaging In a Short-axis Viewmentioning
confidence: 98%
“…others, such as Konofagou et al [17] and d'hooge et al [18], increased the frame rate of the rF images to above 200 Hz by reducing the size of the field of view and the total number of rF imaging lines. Kanai et al [19], [20] used a sparse sector-scan format, in which the number of ultrasound beams was decreased to about 16 to achieve the peak frame rate of 450 Hz. The onset of "pulsive waves" in the heart wall at end-systole and the propagation of spontaneous vibrations was estimated using a phased-tracking method in human subjects [6], [19], [21], [22].…”
mentioning
confidence: 99%
“…(12) Effects of large value of β: Doppler sidebands with mean frequency and its harmonics cannot be ignored if β value is large [44]. (13) Systematic error in zero-crossing: In the measurement of angular velocity vibrations of rotating shafts, the zero-crossing method introduces a systematic error dependent on the frequency of the vibration harmonic [72]. (14) Pull-in-range of PLL: Frequency demodulation as well as β estimation would be possible only if the carrier frequency variation is within the pull-in-range of the PLL.…”
Section: Issuesmentioning
confidence: 99%